MRI T1 Contrast-Enhanced Signal Intensity Is a Prognostic Indicator of Imatinib Therapy in Desmoid-Type Fibromatosis - Zhu, Hui Ci; Xu, Shi Xing; Li, Xiao Ting; Guan, Zhen; Li, Shu; Sun, Ying-Shi (Frontiers in Oncology, 2021)
Objective. To investigate the efficiency of pre-therapy magnetic resonance imaging (MRI) features in predicting the prognosis of desmoid-type fibromatosis patients treated with imatinib. Materials and Methods. A total of 38 desmoid-type fibromatosis patients treated with imatinib were collected in this retrospective study. The high signal intensity on pre-therapy MRI was evaluated on axial T2 and T1 contrast-enhanced sequences with fat suppression. Cox regression and Kaplan–Meier analyses explored the correlation between clinical or radiographic characteristics and progression-free survival (PFS). Results. Hyperintense T1 contrast enhancement (CE) proportion (≥75%) was identified as an independent predictor for PFS. Patients with hyperintense T1 CE proportion <75% demonstrated no progression, while patients with hyperintense T1 CE proportion ≥75% demonstrated a progression rate of 78.4%. Conclusion. Hyperintense T1 CE proportion in the tumor is a potential predictor of disease progression in patients with desmoid-type fibromatosis treated with imatinib. Hyperintense T1 CE proportion <75% indicates progression-free during treatment.